Fractionated radiotherapy initiated at the early stage of bone metastasis is effective to prolong survival in mouse model - Yun Zhang; Zhunyi Gao; Ziwei Qi; Jiahe Xu; Jiao Xue; Lujie Xiong; Junhui Wang; Yuhui Huang; Songbing Qin (Cancer Biology & Therapy)
Background and purpose Bone metastasis is common for breast cancer and associated with poor prognosis. Currently, radiotherapy (RT) serves as the standard treatment for patients exhibiting symptoms of bone metastasis to alleviate pain. Whether earlier application of RT will better control bone metastasis remains unclear.Methods We utilized a mouse model of breast cancer bone metastasis by intra-femoral injection of 4T1-luc breast tumor cells. The bone metastasis was treated by RT using various doses, timings, and modalities. Tumor growth was assessed through bioluminescence imaging, and lung metastases was quantified following lung tissue fixation. Flow cytometry was employed to analyze alterations in immune cell populations.Results Single high-dose RT suppressed tumor growth of bone metastases, but caused severe side effects. Conversely, fractionated RT mitigated tumor growth in bone metastases with fewer adverse effects. Fractioned RT initiated at the early stage of bone metastasis effectively inhibited tumor growth in the bone, suppressed secondary lung metastases, and prolonged mouse survival. In line with the known pro- and anti-metastatic effects of neutrophils and T cells in breast cancer, respectively, earlier fractioned RT consistently decreased the proportions of neutrophils while increased the proportions of T cells in both the bone and the lung tissues.Conclusion The data suggest that fractionated RT can inhibit the progression of early stage of bone metastasis and reduce secondary lung metastasis, leading to favorable outcomes. Therefore, these findings provide preclinical evidence to support the application of fractionated RT to treat patients with bone metastasis as earlier as possible.